2015
DOI: 10.1063/1.4916606
|View full text |Cite
|
Sign up to set email alerts
|

Study of electron transport in hydrocarbon gases

Abstract: The drift velocity and the effective ionization coefficient of electrons in the organic gases, C2H2, C2H4, C2H6, CH3OH, C2H5OH, C6H6, and C6H5CH3, have been measured over relatively wide ranges of density-reduced electric fields (E/N) at room temperature (around 300 K). The drift velocity was measured, based on the arrival-time spectra of electrons by using a double-shutter drift tube over the E/N range from 300 to 2800 Td, and the effective ionization coefficient (α − η) was determined by the steady-state Tow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
20
2

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(31 citation statements)
references
References 17 publications
(19 reference statements)
6
20
2
Order By: Relevance
“…Kondo and Tagashira [6] introduced new electron transport coefficients called α parameters, which are defined by arrival-time spectra of an electron swarm, and reported that the α parameters are related to D 3L . Arrival-time spectra of an electron swarm can be measured by a double-shutter drift tube, and the procedure for obtaining the α parameters from the measured arrival time spectra is well established [7][8][9][10][11][12][13][14][15]; therefore, there is a possibility that values of D 3L are obtained experimentally by the α parameters.…”
Section: Introductionmentioning
confidence: 99%
“…Kondo and Tagashira [6] introduced new electron transport coefficients called α parameters, which are defined by arrival-time spectra of an electron swarm, and reported that the α parameters are related to D 3L . Arrival-time spectra of an electron swarm can be measured by a double-shutter drift tube, and the procedure for obtaining the α parameters from the measured arrival time spectra is well established [7][8][9][10][11][12][13][14][15]; therefore, there is a possibility that values of D 3L are obtained experimentally by the α parameters.…”
Section: Introductionmentioning
confidence: 99%
“…In case of ethanol vapour, our results agree well with those of Hasegawa's and Date's for the E/N range of 1.5-3 kTd. Furthermore, results from Hasegawa [46] and Raether [48] (as presented by von Engel in [49]), in the overlapping range of E/N (140-700 Td), differ from each other (Fig. 3b) by a large factor, even greater than 3, the effective ionization coefficients from Raether [48] being much smaller.…”
Section: Resultsmentioning
confidence: 72%
“…Hasegawa's and Date's results for methanol [46] cover the region of much lower values of the reduced electric fields, from 130 Td to 3 kTd. For the overlapping range of E/N , our effective ionization coefficients in methanol vapor are slightly lower than those in the work of Hasegawa and Date (Fig.…”
Section: Resultsmentioning
confidence: 89%
See 2 more Smart Citations